Aquifer Area Investigation Using Resistivity Method in Cikopomayak, West Java, Indonesia - Josua Washington Sihotang; Rodrigo Osvaldus; Danny Bona Tua Munte; Nasib Priono; Febriwan Mohamad (Himpunan Ahli Geofisika Indonesia (HAGI), 2018)
Administratively, the research area is located in around Cikopomayak Village, Jasinga, Bogor, West Java,Indonesia. Based on the Hydrogeological and Groundwater Basin Map, this research area was classied to non-potential groundwater basin. In addition, when the summer comes, the lack of water will be happened around the area. Consequently, the water reserve wasn't enough to fulll the necessity of freshwater. Thus, the research about identifying aquifer location was needed. This research aims to determine the depth and thickness of aquifer for the alternative ways to overcome the problem, particularly, for the Cikopomayak Village. Theresearch used the geophysical method by modeling the several data such as Geoelectric 1-D to know the aquifer location based on the section of medium resistivity value. Then, the geoelectric data was correlated to the borehole drilling data that is Gamma Ray (GR) Log, Spontaneous Potential (SP) Log, Resistivity Log, and the cutting data. Commonly, the most suitable lithology for an aquifer is sandstone because of its good characteristic of permeability and porosity. Logging data result will show the small value of GR log, SP Log lean-ing to the right, and low-value resistivity for indicating the aquifer zone. Based on geoelectric data, the research zone has 3 groups of resistivity value and lithology that are shaly clay-stone and siltstone with low-value resistivity (0-50 ohm.m), sandy claystone, medium sandstone, and coarse sandstone with medium value resistivity (50-150 ohm.m), fine sand-stone, sandy claystone, and andesite with high-value resistivity (> 150ohm.m). The aquifer system in the research area was classied into 3 groups that are aquifer, aquitard, andaquiqlud.